FAKTOR – FAKTOR PENENTU HARGA SAHAM - Syahzuni, Barlia Annis; Juwandita Ansita2, Desy Prastyani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Recently, several coal industries are facing a significant decline in share prices so that the purpose of this study is to know empirically the effect of profitability, liquidity and solvency on stock prices either partially or simultaneously in coal sub-sector companies listed on the Indonesia Stock Exchange in the 2017-2019 period. This study uses a type of causal comparative research (causal comparative research) which is used to see the relationship between cause and effect on two or more variables. The sample in this study is coal companies listed on the Indonesia Stock Exchange for the period 2017-1029 using the purposive sampling method. There are 12 companies that meet the criteria for the research sample, so that the sample is 36 financial statements. The results showed that partially there was a significant and significant influence of the profitability (ROE) and solvency (DER) variables on stock prices, while the liquidity variable (CR) had no effect on stock prices. Simultaneously there is the influence of the variable profitability (ROE), liquidity (CR), solvency (DER) on stock prices.